Loyal Consumers: Efforts to Improve and Maintain Consumer Databases Using Youtube Optimization Techniques - Wibowo, Kresno Ario Tri; Muzakki, Muhammad Husin Nur (Universitas Aisyiyah Surakarta, 2023)
This study tries to test the ranking model on youtube search. Youtube brings up search results based on the number of visits and video recommendations available. The method used in this research begins by collecting 10 keywords that appear in a youtube search. Of the 10 results will be used as the image file name to be used. The 10 image files are then turned into a video. The link generated from the upload process is then registered with a free ping service on the internet. For testing, day parameters are used, namely 1 day, 2 days and 3 days. Within 3 days the video has appeared on the first page of a Google search with keywords that match the names of the image files.